Nucleotide Analysis in Korean Dairy Products Using High- Performance Liquid Chromatography with Diode Array Detector - Won, Jong-Eun (Food Sci Anim Resour, 2019)
Nucleotides play important roles in numerous intracellular biochemical processes and are used in infant formulas and other dairy products. However, domestic analytical methods for assessing nucleotide content in products have not yet been established, and therefore, methods for determining nucleotide content are urgently required. A rapid and simple analytical method for determining the content of five types of nucleotides in dairy products was improved using solid phase extraction clean-up and high-performance liquid chromatography with diode array detector. The extraction solvent used in the AOAC method was not well dissolved and was changed to hydrophilic EDTA-Na. In addition, the results obtained using the isocratic elution method and a single wavelength were similar to those obtained using the AOAC method, and the time taken for analysis was shortened from 40 min to 25 min. The process of method validation revealed the following parameters: accuracy (84.69%–102.72%), precision (1.51%–6.82%), linearity (0.999), and limit of detection (cytidine 5′-monophosphate, 0.09 mg/L; uridine 5′-monophosphate, 0.11 mg/L; adenosine 5′-monophosphate, 0.12 mg/L; guanosine 5′-monophosphate, 0.11 mg/L; and inosine 5′-monophosphate, 0.14 mg/L). The method was also used to determine the nucleotide concentration in 25 samples (infant formulas, 1.99–29.39 mg/100 g; and cow milk, 0.28–0.83 mg/100 g). The newly improved method was appropriate for analyzing nucleotides in infant formulas and other dairy products faster when compared to conventional methods.